(3GdWH GdLOjO GdcjejGFjs - (3HQGcdShSs
(3ChdgG (B:s
(3GdMeO ddg GdP Ndb GdGfSGf hGgOGg Gdj HjGf GdHjGf hHYO agPG cJGH GdWH GdLOjO GdcjejGFj GdPj GNJQYg HQcdhS jTJed Ydi ebGdGJ s
(3BNQgG (B:s
(3ef BNQ GdehLhO hYfg HdhQj gh aVdI dG jOd Ydi TF hGdjGbhJj dg eQGJH HMSH RjGOI GdcHQjJjI hfbUGfgG hGNJdGWgG HGdRFHb Ch GdedM s
(3Vef eLehY , JQJjHgG (B: 2s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3HQdjf (B- (3JhHfLjf (B(1969) s
Keywords: (3GdcjejGA h GdWHjYjGJs